Functional conservation and divergence of miR156 and miR529 during rice development - Yan Li; Yizhou He; Tian Qin; Xuelian Guo; Kun Xu; Chunxue Xu; Wenya Yuan (Crop Journal, 2023)
MicroRNAs (miRNAs) are important regulatory elements involved in the regulation of various plant developmental and physiological processes by blocking the expression of target genes. MiR156 and miR529 are two combinatorial regulators, which cooperatively target the SQUAMOSA PROMOTER BINDING-LIKE (SPL) family genes. However, there has been no report about the functional conservation and divergence of miR156 and miR529 during plant development to date. In this study, the biological function and relationship of miR156, miR529 and their target OsSPL14 in rice were explored. Overexpression of miR156e or miR529a (miR156e-OE and miR529a-OE) increased the grain size and tiller number but decreased the plant height and panicle length, while an opposite phenotype was observed for their target mimicry (miR156-MIMIC and miR529a-MIMIC) transgenic plants. Stem-loop RT-PCR results revealed ubiquitous expression of miR156 in roots, axillary buds and leaves, while miR529 was preferentially expressed in the panicle. Accordingly, OsSPL14 could be preferentially and precisely cleaved by miR529a in young panicle but by miR156 in vegetative tissues. Transgenic plants generated by the target immune strategy exhibited obvious growth defects upon the blocking of miR156 and/or miR529 function in rice, confirming that both miR156 and miR529 play important roles in controlling rice growth and development. Moreover, the miR156/miR529-OsSPL14 module negatively controlled grain size by regulating the genes associated with grain size and cell cycling, and controlled plant height through a more complicated mechanism. Taken together, our results demonstrate that miR156 and miR529 respectively function dominantly in the vegetative stage and reproductive stage to control rice growth and development by regulating the accumulation of OsSPL14. These findings facilitate a better understanding of the functional conservation and divergence of miR156 and miR529 family in the miRNA combinatorial regulatory network of plants.